Dispatching emergency reserves - Van de Venter, Al ' louise (Department of Electrical Engineering, 2015)
This dissertation presents the analysis of cost-effective dispatching of emergency reserves with a specific focus on supply and demand side options. On the demand side options the focus is the demand market participation product. On the supply side options the use of hydro and gas specifically the open cycle gas turbines are studied. In capacity constraint systems, supplying the demand with the current generation mix needs to be met. With a diminishing reserve margin and increase in demand yearly this challenge increases. The South African scenario is reported in this paper. As demand grows the ability to meet that demand remains a focus; a responsibility that remains a priority for the system operator. In times of surplus or shortage generation with adequate or diminishing reserve margins the focus on dispatching optimally and economically is an important aspect. Currently the South African Interconnected Power System is constrained; at times there is more demand than supply. The reserve categories are the ancillary requirements and are different for all power systems. Reserves are to cater for disturbances on the power system to ensure a healthy frequency is maintained. Reserve categories according to the ancillary requirements are: instantaneous, regulating, ten minute, supplemental and emergency. This dissertation focuses on emergency reserve.